The Trapping Index: How to integrate the Eulerian and the Lagrangian approach for the computation of the transport time scales of semi-enclosed basins. Issue 1 (15th September 2015) - Cucco, Andrea; Umgiesser, Georg
Highlights: Transport Time Scales (TTS) were computed for semi-enclosed basins. TTS cannot be used univocally to compute basins flushing features. A so-called Trapping Index (TI) analyses was proposed. The TI analysis was helpful to individuate areas where water can be entrapped in. The TI analysis is an integrative approach to the computation of the TTS. Abstract: In this work, we investigated if the Eulerian and the Lagrangian approaches for the computation of the Transport Time Scales (TTS) of semi-enclosed water bodies can be used univocally to define the spatial variability of basin flushing features. The Eulerian and Lagrangian TTS were computed for both simplified test cases and a realistic domain: the Venice Lagoon. The results confirmed the two approaches cannot be adopted univocally and that the spatial variability of the water renewal capacity can be investigated only through the computation of both the TTS. A specific analysis, based on the computation of a so-called Trapping Index, was then suggested to integrate the information provided by the two different approaches. The obtained results proved the Trapping Index to be useful to avoid any misleading interpretation due to the evaluation of the basin renewal features just from an Eulerian only or from a Lagrangian only perspective.